2016
DOI: 10.1021/acsami.6b00360
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lateral Ordering in Cylinder Forming PS-b-PMMA Block Copolymers Exploiting the Entrapped Solvent

Abstract: The self-assembly of block copolymer (BCP) thin films produces dense and ordered nanostructures. Their exploitation as templates for nanolithography requires the capability to control the lateral order of the nanodomains. Among a multiplicity of polymers, the widely studied all-organic polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA) BCP can easily form nanodomains perpendicularly oriented with respect to the substrate, since the weakly unbalanced surface interactions are effectively neutralized by graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 62 publications
5
56
0
Order By: Relevance
“…Moreover, in a vacuum environment, the polymer swelling kinetics can be distinguished from the slow vapor pressure build-up (minutes) in a standard ambient SVA cell. Other approaches include SVA at elevated temperatures [146,198] and the use of a solvent-trapping layer underneath the block copolymer thin film during thermal annealing [212]. Chavis et al [218] reported a real-time in-situ SVA on a symmetric PHEMA-b-PMMA DBCP using a methanol and THF mixture (THF and methanol are selective for PMMA and for PHEMA, respectively).…”
Section: New Approaches To Svamentioning
confidence: 99%
“…Moreover, in a vacuum environment, the polymer swelling kinetics can be distinguished from the slow vapor pressure build-up (minutes) in a standard ambient SVA cell. Other approaches include SVA at elevated temperatures [146,198] and the use of a solvent-trapping layer underneath the block copolymer thin film during thermal annealing [212]. Chavis et al [218] reported a real-time in-situ SVA on a symmetric PHEMA-b-PMMA DBCP using a methanol and THF mixture (THF and methanol are selective for PMMA and for PHEMA, respectively).…”
Section: New Approaches To Svamentioning
confidence: 99%
“…To promote perpendicular orientation of the domains in the PS-b-PMMA BCP thin films, poly (styrene-random-methyl methacrylate) (P(S-r-MMA)) random copolymer (RCP) (molecular weight, Mn = 69 kg/mol, Styrene fraction, fs = 0.61, polydispersity index, PDI = 1.19) was grafted (RTA: T = 310 °C, t = 60 s) on hydroxyl terminated Si surface to form a neutral ≈ 19 nm thick brush layer. This thick RCP brush layer provides a reservoir of embedded solvent [29,30,33] able to sustain the ordering process in the phase separated PS-b-PMMA film over several decades of time during the SARTA treatment. [29] The all-organic PS-b-PMMA BCP exhibits S-MMA parameter that is weakly dependent on T, because the entropic contribution (0.021) is much larger than the enthalpic one (3.2/T).…”
Section: Textmentioning
confidence: 99%
“…The measured  value can be treated following the time-Temperature superposition (tTS) procedure, to describe the ordering kinetics. [29,32]  as a function of tA for different TA are collected in a master curve at the reference TA (Table 1) Table 1). Interestingly  is not constant within the cylindrical morphology but it is N-dependent, that is, basically, it depends on the driving force for the phase separation.…”
Section: Textmentioning
confidence: 99%
“…As the vertical orientation of the nanofeatures occurs for a wide range of DBC film thickness [33,[41][42][43] these DBCs represent interesting scaffolds for the synthesis of lithographic masks with stripes or vertical pillars having tailored characteristic dimensions and heights. The lateral order within the nanodomains is controlled by the annealing time and temperature, eventually exploiting the residual solvent trapped in the polymeric film [44,45]. Topographical [46][47][48] or chemical pre-pattering [49,50] of the substrate allows registering the in-plane orientation of the nanodomains thus further improving the lateral order.…”
Section: Bcps Backgroundmentioning
confidence: 99%